Nasal cryptococcosis in a sheep in Brazilian Semi-Arid - Silva, Saulo T. Gusmão da; Souza, José C. de Almeida; Mendonça, Carla L. de; Izael, Marisa A.; Dantas, Antônio F.; Portela, Roseana; Riet-Correa, Franklin; Afonso, José A. Bastos (Brazilian Journal of Veterinary Pathology, 2010)
A case of nasal cryptococcosis is reported in a two years old male hair sheep in the Brazilian semi-arid. Severe respiratory signs and a mass occupied a large portion of the right nasal cavity were observed. Cryptococcosis was diagnosed by the typical histologic appearance of the fungus.